THE EFFECT OF EDUCATION LEVEL, WORK EXPERIENCE AND WORK ENVIRONMENT ON JOB SATISFACTION THROUGH JOB MOTIVATION AS INTERVENING VARIABLES IN THE PLANNING, RESEARCH AND DEVELOPMENT AGENCY OF KARIMUN DISTRICT - Syahril, Syahril; Indrayani, Indrayani; Catrayasa, I Wayan; Gaddafi, Muammar (RADJA PUBLIKA, 2022)
This study was conducted to determine the effect of education level, work experience and work environment on job satisfaction through work motivation as an intervening variable. The research method used is descriptive quantitative. Sampling using a survey method technique with the total population as a sample of 73 respondents. The data collection technique used an instrument in the form of a questionnaire to be analyzed. The instrument was calibrated using item validity and reliability coefficients using SEM-PLS analysis with the help of SmartPLS software. From the research results, it is known 1).education level has a significant effect on work motivation, 2).work experience directly has a significant effect on work motivation, 3).work environment directly has a significant effect on work motivation, 4).work motivation directly has a significant effect on job satisfaction, 5).level of education directly does not have a significant effect on job satisfaction, 6).work experience directly has a significant effect on job satisfaction, 7).work environment has a direct and insignificant effect on job satisfaction, 8).The level of education indirectly has a significant effect on job satisfaction through work motivation, 9).work experience indirectly has a significant effect on job satisfaction through work motivation, 10).The work environment indirectly has a significant effect on job satisfaction through work motivation.The coefficient of determination of the model of education level, work experience and work environment on job satisfaction is 0.462, meaning that job satisfaction can be influenced by education level, work experience and work environment by 46.2% and the remaining 53.8% is influenced by other variables outside research, while the model of education level, work experience and work environment on work motivation is 0.451, meaning that work motivation can be influenced by education level, work experience and work environment by 45.1% and the remaining 54.9% is influenced by other variables outside study.